Weak Type Estimate of Singular Integral Operators on Variable Weak Herz-Type Hardy Spaces - Boulares, Hamza Brahim; Drihem, Douadi; Hebbache, Wafa (Armenian Journal of Mathematics, 2023)
This paper is concerned with the boundedness properties of singular integral operators on variable weak Herz spaces and variable weak Herz-type Hardy spaces. Allowing our parameters to vary from point to point will raise extra difficulties, which, in general, are overcome by imposing regularity assumptions on these exponents, either at the origin or at infinity. Our results cover the classical results on weak Herz-type Hardy spaces with fixed exponents.